2022
DOI: 10.3389/fonc.2022.949534
|View full text |Cite
|
Sign up to set email alerts
|

Azacitidine and donor lymphocyte infusion for patients with relapsed acute myeloid leukemia and myelodysplastic syndromes after allogeneic hematopoietic stem cell transplantation: A meta-analysis

Abstract: BackgroundFor patients with relapsed acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) after allogeneic hematopoietic stem cell transplantation (allo-HSCT), azacitidine with donor lymphocyte infusion (DLI) is a feasible option to perform a preemptive or salvage treatment. However, its efficacy lacked comprehensive analysis, and this study aimed to fill this gap.MethodsWe searched potential studies in PUBMED, EMBASE, and the Cochrane Central Register of Controlled Trials. Thirteen studies involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The to be only 11%−30%. 20,21 Studies have shown that the application of pro-DLI in the haploidentical setting could help 49.1%−67.8% of the patients with MNs experience long-term survival and decrease the relapse to 14.7%−32.4%. [22][23][24] While, there is limited experience with use of pro-DLI in pediatric MN patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The to be only 11%−30%. 20,21 Studies have shown that the application of pro-DLI in the haploidentical setting could help 49.1%−67.8% of the patients with MNs experience long-term survival and decrease the relapse to 14.7%−32.4%. [22][23][24] While, there is limited experience with use of pro-DLI in pediatric MN patients.…”
Section: Discussionmentioning
confidence: 99%
“…GVL effects make DLI currently one of the most common interventions used for post‐transplant relapse of hematological malignancies. However, unlike chronic myeloid leukemia, MNs recurring after allo‐HSCT do not respond well to DLI, with OS rates reported to be only 11%−30% 20,21 . Studies have shown that the application of pro‐DLI in the haploidentical setting could help 49.1%−67.8% of the patients with MNs experience long‐term survival and decrease the relapse to 14.7%−32.4% 22 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, the association between DLI, Azacitidine (AZA), and Venetoclax in 26 AML patients who relapsed after transplant has been recently published with an overall response rate of 61.5% (voce 98 di Bonifazi diventa (6). (7) focused their attention on the use of AZA and DLI in their meta-analysis. Searching in PUBMED, EMBASE, and Cochrane Central Register of Controlled Trials, they found and analyzed 13 studies involving 811 patients.…”
mentioning
confidence: 99%
“…( 7 ) focused their attention on the use of AZA and DLI in their meta-analysis. Searching in PUBMED, EMBASE, and Cochrane Central Register of Controlled Trials, they found and analyzed 13 studies involving 811 patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation